DIVERSIFIKASI PRODUK OLAHAN IKAN LELE UNTUK PEMBERDAYAAN EKONOMI MASYARAKAT DESA SIGUMURU - Rambe, Muhammad Rahman; Nasution, Alvi Sahrin; Pohan, Rizky Febriani (Jurnal Abdi Insani, 2025)
Catfish is a type of freshwater fish with high economic value, both in terms of sales value and nutritional value. Furthermore, this fish is easy to grow, with a high protein content, soft, white meat, and affordable prices. However, suboptimal cultivation results in low yields, which reduces the income of catfish farmers. One effort to increase the income of catfish farmers is through diversification of processed catfish products (catered fish paste, catfish meatballs, and catfish satay). This activity aims to improve the knowledge and skills of the Sigumuru Village community in processing catfish into a variety of processed products. Furthermore, this activity can also increase the income of the Sigumuru Village community. The methods used in this activity were location surveys, socialization, demonstrations, marketing, and monitoring. The participants of this activity were the Fish Cultivation Group (FCG) "Sigumuru Jaya" which consisted of 12 people. This activity was carried out for 8 months. The activity evaluation method was carried out using a pre-test, post-test, preference questionnaire, and monitoring questionnaire. The results of this activity showed an average increase in community empowerment outcomes of 83.89% which consisted of increased skills, knowledge, business sustainability, and partner income. However, the overall activities carried out showed an increase in community empowerment outcomes of 91.11%. The results of the preference questionnaire showed that the majority of the community (50%) chose pecal lele as the most popular processed catfish product because it tastes good (37.5%). The results of the monitoring questionnaire showed an assessment score of 75. Pecal lele is the most popular food among the community. Thus, the PKM team recommends that target partners further increase pecal lele production to increase their income and business sustainability.